Biomechanical analysis of fundamental human movements - Chapman, Arthur E. 1941- (Human Kinetics, 2008)
Uses mechanical, mathematical and biological definitions and concepts and the application to human movements. This book provides a brief introduction to the elements of biomechanical analyses and the principles that underlie human motion and then delves into an array of fundamental human movements and their components